CellSearch® technology applied to the detection and quantification of tumor cells in CSF of patients with lung cancer leptomeningeal metastasis. Issue 2 (November 2015) - Tu, Qian; Wu, Xianglei; Le Rhun, Emilie; Blonski, Marie; Wittwer, Basile; Taillandier, Luc; De Carvalho Bittencourt, Marcelo; Faure, Gilbert C.
Highlights: This is a pilot study in patients with LM due to lung cancer. It focused on detecting CSFTC according to an adapted CellSearch ® technology. Of 18 LM patients enrolled, 14 were detected CSFTCs. CSFTC clusters were common in CSF of lung cancer patients with LM. Abstract: Objectives: The diagnosis of solid cancer leptomeningeal metastasis (LM) relies on the cytology of cerebrospinal fluid (CSF) and/or imaging evidence of neuraxis, yet both lack sufficient sensitivity. The utility of the CellSearch ®, an FDA -approved technology, in assessing CSF tumor cell (CSFTC) was evaluated here in the diagnosis and treatment of patients with lung cancer-related LM. Materials and methods: In 18 patients with magnetic resonance imaging (MRI) confirmed LM due to lung cancer, 5 mL of CSF were collected in CellSave ® preservative tubes, which allow performing the assay within 96 h after sampling. Using a previously adapted CellSearch ® method, we detected, visualized and enumerated CSFTCs and compared the results with conventional cytology. In 3 patients, tumor cells were evaluated sequentially to explore the predictive role of CSFTCs enumeration in the treatment response monitoring. Results: CSFTCs were disclosed in 14 of 18 MRI confirmed LM samples (median 785CSFTCs/5 mL CSF, range 1 to >20, 000), yielding a sensitivity of 77.8%, compared with 44.4% for conventional cytology. CSFTC clusters were observed in 12 patients, similar to those previously described in blood as circulating tumor microemboli (CTM), and enumerated sequentially with reproducible results, which did not necessarily correlate with response to treatment. Conclusion: The CellSearch ® technology, applied to limited sample volumes and allowing delayed processing, could be of great interest in the diagnosis of LM in lung cancer patients.